SHADES OF VENICE IN THE BIOGRAPHY OF HEGUMEN PALLADY ROGOVSKY - Alex YASTREBOV (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2014)
Pallady Rogovsky was the fi rst Russian doctor of theology and philosophy. While a student of the Slavyano-Greek-Latin Academy directed by the Brothers Lichudes, he left his homeland for the West in order to obtain a full university education. The years which he spent in Europe and particularly in Italy have attracted little notice on the part of Church historians. The study of unpublished materials in Italian archives together with those already published by the Russian researcher E. Shmurlo from the archive of the Propaganda de Fide and the Greek College, which however, remain unnoticed for the great majority of academics, permit us to have an idea of what occupied Rogovsky during this time, as well as to draw a more precise portrait of his personality. Most remarkable is the fact of his priestly ordination in the Roman Catholic Church and the correspondence relating to Rome’s acceptance of his Russian Orthodox diaconal ordination. One of the most informative documents found among those relating to his ordination and addressed to the Roman Curia is the letter of a Russian Catholic, the deacon (later defrocked) Petr Artem’ev, in which Artem’ev revealed that Rogovsky already had converted to Roman Catholicism before he left Russia. Equally noteworthy is Rogovsky’s own letter which he composed while in Venice and in which he formulated his plans for the propagation of Roman Catholicism in Russia.